Variables determining response to intensive intervention in pre-school language impaired children. - Mulligan, Jennifer (My University, 2008)
This was a comparative longitudinal study of the files of 50 children who attended intensive language therapy at The Centre for Language and Hearing Impaired Children over the past 8 years. The research compared initial and final assessment results to determine what specific language areas improve when children attend an intensive therapeutic pre-school environment. A paired comparison t-test with a 95% (alpha = 0.05) level of confidence was used to determine whether the difference between the initial and final assessments was statistically significant. The study also examined and described associated child and family specific variables such as: previous assessments and therapy, gender, pregnancy and birth, birth order, feeding, developmental milestones, medical history, ear infections, family history of disorders, behavioural and emotional issues, medication, play, fine and gross motor development, parental education level and referral to primary school. The sample of children was then grouped into severity and types of language impairment: moderate receptive and expressive language impairment, severe receptive and expressive language impairment, and moderate expressive language impairment. These groups were analysed and described in terms of associated variables, degree of improvement made in receptive and expressive language ability, as well as variables which may influence progress including number of associated variables, age of admission and length of time attending The Centre for Language and Hearing Impaired Children. The findings of this study were statistically significant for intensive intervention in receptive grammatical morphology, receptive syntax, expressive vocabulary in the initial stages of intervention, and expressive syntax, indicating that intensive structured language intervention was effective for this population of language impaired children. Receptive vocabulary was the only language area in the study that did not improve, and this finding highlights the importance of assessment and direct intervention for receptive abstract vocabulary. Certain associated variables manifested more frequently than others in the case history profiles of this population of language impaired children, specifically behavioural problems, medical issues, a family history of related difficulties, and delay in first word and first sentence production. Overall, the number of associated factors in this study had a cumulative effect in determining severity of the impairment, but did not appear to negatively impact progress in intervention. In many of the language areas where catch-up improvement occurred, a high number of associated factors was found. Age at admission and amount of time spent at The Centre for Language and Hearing Impaired Children appeared to be important factors in determining catch-up improvement in the various language areas of this population, particularly the severely impaired children. The limitations of this study and related thoughts for future research are discussed.